A conductive cell‐imprinted substrate based on CNT–PDMS composite. (1st April 2019) - Kavand, Hanie; Rahaie, Mahdi; Koohsorkhi, Javad; Haghighipour, Nooshin; Bonakdar, Shahin
Abstract: Cell function regulation is influenced by continuous biochemical and biophysical signal exchange within the body. Substrates with nano/micro‐scaled topographies that mimic the physiological niche are widely applied for tissue engineering applications. As the cartilage niche is composed of several stimulating factors, a multifunctional substrate providing topographical features while having the capability of electrical stimulation is presented. Herein, we demonstrate a biocompatible and conductive chondrocyte cell‐imprinted substrate using polydimethylsiloxane (PDMS) and carbon nanotubes (CNTs) as conductive fillers. Unlike the conventional silicon wafers or structural photoresist masters used for molding, cell surface topographical replication is challenging as biological cells showed extremely sensitive to chemical solvent residues during molding. The composite showed no significant difference compared with PDMS with regard to cytotoxicity, whereas an enhanced cell adhesion was observed on the conductive composite's surface. Integration of nanomaterials into the cell seeding scaffolds can make tissue regeneration process more efficient.